KOMPOSISI UNSUR KIMIA PADA ABU AMPAS TEBU DENGAN VARIASI SUHU PEMBAKARAN AKHIR - Anisah; Lucas Letournel; Aulia Mufti Salsabila; Yusrina Luthfiana; Nurul Anisa (LPPM Universitas Negeri Jakarta, 2023)
Cement production worldwide contributes at least a 9% increase in CO2 emissions. Industrial or agricultural waste can cause serious problems for the environment. One of the wastes that can be used as SCM from agricultural waste is sugar cane. This research was conducted to determine the content of chemical elements contained in bagasse ash which is suspected to have chemical content similarities with cement. This study uses an experimental method, with the type of pre-experiment research which has a one shot study case type research scheme. The results indicated that bagasse ash with a final combustion temperature of 600C had the highest silicon content compared to bagasse ash with a final firing temperature of 500C and 700C. The analysis results indicate that with a relatively high percentage of silicon, bagasse ash with a combustion temperature of 600C can be used as an additive or cement substitute.